2018
DOI: 10.1177/1461444818774256
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ mobile relational maintenance in resource-constrained contexts: Barriers and facilitating access conditions

Abstract: Mobile phones have become central to family members' daily communication. This study investigates the material and skills access barriers that parents of adolescents in resourceconstrained contexts face for mobile relational maintenance. Following an exploratory sequential mixed-methods design, interviews with parents in Bogotá, Colombia explored how they managed to keep in touch with their children despite facing access barriers and how these barriers still affected their parent-child mobile interactions. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Teknologi digital dapat mencegah masalah dalam keluarga, dan juga sebaliknya teknologi digital dapat menimbulkan masalah dalam keluarga (Barrie et al, 2019). Penelitian mengenai keluarga dan teknologi digital sudah banyak dilakukan, penelitian-penelitian tersebut berfokus pada: 1) dampak penggunaan teknologi digital bagi internal keluarga (Barrie et al, 2019;Dong et al, 2021;Setiansah et al, 2019;Velasquez, 2018); 2) latar belakang keluarga yang menjadi penyebab kesenjangan digital (Bonal & González, 2020;Katz et al, 2019;Liu & Wang, 2021;Scheerder et al, 2019bScheerder et al, , 2020Zhang et al, 2020;Zhong et al, 2021); 3) Peran keluarga dan/atau anggota keluarga dalam penggunaan teknologi digital anggota keluarga lainnya (Dong et al, 2021;Katz et al, 2019;Plaza-De-La-Hoz & Caro, 2018;Rosales & Blanche-T, 2021;Xiong & Zuo, 2019) Melihat fokus penelitian-penelitian yang sudah ada sebelumnya, bisa diamati bahwa situasi problematis yang dihadapi keluarga didasari pada kondisi keluarga yang didalamnya terdiri dari anggota keluarga yang berbeda umur atau generasi (keluarga lintas generasi). Hasil studi penelitian Barrie, John, dan Timothy (2019) menyebutkan bahwa teknologi komunikasi digital saat ini memainkan peran yang beragam dalam kehidupan keluarga lintas generasi.…”
Section: Pendahuluanunclassified
“…Teknologi digital dapat mencegah masalah dalam keluarga, dan juga sebaliknya teknologi digital dapat menimbulkan masalah dalam keluarga (Barrie et al, 2019). Penelitian mengenai keluarga dan teknologi digital sudah banyak dilakukan, penelitian-penelitian tersebut berfokus pada: 1) dampak penggunaan teknologi digital bagi internal keluarga (Barrie et al, 2019;Dong et al, 2021;Setiansah et al, 2019;Velasquez, 2018); 2) latar belakang keluarga yang menjadi penyebab kesenjangan digital (Bonal & González, 2020;Katz et al, 2019;Liu & Wang, 2021;Scheerder et al, 2019bScheerder et al, , 2020Zhang et al, 2020;Zhong et al, 2021); 3) Peran keluarga dan/atau anggota keluarga dalam penggunaan teknologi digital anggota keluarga lainnya (Dong et al, 2021;Katz et al, 2019;Plaza-De-La-Hoz & Caro, 2018;Rosales & Blanche-T, 2021;Xiong & Zuo, 2019) Melihat fokus penelitian-penelitian yang sudah ada sebelumnya, bisa diamati bahwa situasi problematis yang dihadapi keluarga didasari pada kondisi keluarga yang didalamnya terdiri dari anggota keluarga yang berbeda umur atau generasi (keluarga lintas generasi). Hasil studi penelitian Barrie, John, dan Timothy (2019) menyebutkan bahwa teknologi komunikasi digital saat ini memainkan peran yang beragam dalam kehidupan keluarga lintas generasi.…”
Section: Pendahuluanunclassified
“…The unequal access to or adoption of smartphones, computers, and internet is the focus of digital inequality research or digital divide research [8,9]. Research within this domain has repeatedly demonstrated that a significant amount of individuals lack access, knowledge, positive attitudes, skills or support to adopt a smartphone, computer or internet in general as well as for specific uses, such as using a search engine, using a word processor, making new contacts online, or buying a product online, both in developed and developing countries, in disabled and non-disabled populations, among poor and non-poor, and across old and young individuals [6,7,[10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%